THE ADOPTION PROCESS ON INNOVATION OFARTIFICIAL FEEDIN THE KOTO MESJID VILLAGEXIII KOTO KAMPAR SUBDISTRICTKAMPAR REGENCYRIAU PROVINCE - Saragih, Tiarmauli; Kusai, Kusai; Zulkarnain, Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Research on adoption process on innovation ofartificial feed was conducted in March 2018in the Koto Mesjid VillageXIIIKoto Kampar Subdistrict Kampar RegencyRiau Province.This study was aimed to determined the adoption process of artificial feed innovation, knowing factors influence the adoption of artificial feed innovation, and to know the relationship between the factors that influence adoption with the adoption process of innovation of artificial feed. The method used in this research is survey method that is analyzed by descriptive analysis and Rank Spearman and number of respondents in this research are 30 respondents.            From the results of the research analysis, it was found that the adoption process with a total score of 345 is in the fast category and the time required 2-4 months.Factors that influence adoption by total scores of components of innovation traits, types of innovation decisions, communication channels, nature of targets, and extension workers are 2,088, falling under the strongly influencing category.Based on Spearman Rank correlation there is a strong correlation between innovation characteristic, communication channel factor with adoption process and there is a very weak correlation between factor of decision type of innovation, target nature factor, extension factor with adoption process.However, there is an unsignificant relationship between the factors that influence adoption and the adoption process. Keywords: adoption, innovation, artificial feed